Exploring idiosyncratic deal arrangements in a technology-based organisation - Sibongile Tshabalala; Nelesh Dhanpat (SA Journal of Human Resource Management)
Orientation: This research examines the dynamics of South Africa’s technology sector, focussing on how technology professionals navigate idiosyncratic deal (i-deal) arrangements.